Multi-disciplinary trends in artificial intelligence : 11th International Workshop, MIWAI 2017, Gadong, Brunei, November 20-22, 2017, Proceedings /: 11th International Workshop, MIWAI 2017, Gadong, Brunei, November 20-22, 2017, Proceedings. (2017) - Unknown
No abstract available